The effect of non-fluoride factors on risk of dental fluorosis: evidence from rural populations of the Main Ethiopian Rift - Kravchenko, J.; Rango, T.; Akushevich, I.; Atlaw, B.; McCornick, Peter G.; Merola, R.B.; Paul, C.; Weinthal, E.; Harrison, C.; Vengosh, A.; Jeuland, M. (Elsevier, 2014)
Elevated level of fluoride (F-) in drinking water is a well-recognized risk factor of dental fluorosis (DF). While considering optimization of region-specific standards for F-, it is reasonable, however, to consider how local diet, water sourcing practices, and non-F- elements in water may be related to health outcomes. In this study, we hypothesized that non-F- elements in groundwater and lifestyle and demographic characteristics may be independent predictors or modifiers of the effects of F- on teeth. Dental examinations were conducted among 1094 inhabitants from 399 randomly-selected households of 20 rural communities of the Ziway–Shala lake basin of the Main Ethiopian Rift. DF severity was evaluated using the Thylstrup-Fejerskov Index (TFI). Household surveys were performed and water samples were collected from community water sources. To consider interrelations between the teeth within individual (in terms of DF severity) and between F- and non-F- elements in groundwater, the statistical methods of regression analysis, mixed models, and principal component analysis were used. About 90% of study participants consumed water from wells with F- levels above theWHO recommended standard of 1.5 mg/l. More than 62% of the study population had DF. F- levels were a major factor associated with DF. Age, sex, and milk consumption (both cow's and breastfed)were also statistically significantly (p b 0.05) associated with DF severity; these associations appear both independently and as modifiers of those identified between F- concentration and DF severity. Among 35 examined elements in groundwater, Ca, Al, Cu, and Rb were found to be significantly correlated with dental health outcomes among the residents exposed to waterwith excessive F- concentrations. Quantitative estimates obtained in our study can be used to explore new water treatment strategies, water safety and quality regulations, and lifestyle recommendations which may be more appropriate for this highly populated region.